Expression of a human U1 RNA gene introduced into mouse cells via bovine papillomavirus DNA vectors. - Schenborn, E T (1985)
We introduced a gene for human U1 small nuclear RNA, HU1-1, into mouse C127 cells via bovine papillomavirus (BPV) vectors. After transfection, up to 15% of the total U1 RNA in transformed cells was encoded by the introduced human genes. High levels of expression of the human gene were observed when the recombinant viral DNAs were maintained either as plasmids or after integration into high-molecular-weight DNA. As few as 400 and 35 base pairs of 5' and 3' flanking region sequences, respectively, were sufficient for transcription of human U1 RNA, and no increase in the level of expression was observed with HU1-1 DNA containing several kilobases of flanking region sequences. Several of the transformed cell lines contained the recombinant BPV DNA apparently integrated into the host genome. Integration or rearrangement or both of the U1-BPV DNA was promoted when the HU1-1 gene was positioned at the BamHI site downstream of the BPV transforming region. At least two variants of the U1-BPV DNAs were able to cause morphological transformation of cells despite the fact that these DNAs lacked a BPV transcriptional enhancer element.